Assessing the intercultural sensitivity of students in an agriculture diversity and social justice course. (2nd October 2018) - Lambert Snodgrass, Lisa; Morris, Pamala V.; Acheson, Kris
ABSTRACT: In an increasingly connected world, the industry of agriculture finds itself at the centre of the challenges of globalisation, including diversity and social equity issues. Recognising the responsibility of the academic discipline of agriculture to respond to these challenges, this study assesses the effectiveness of the interventions in a diversity consciousness–raising course comprised of experiential and reflective activities grounded in critical pedagogy, social development theory, and cognitive development theory as implemented with students in small-group recitation labs. The impact of the interventions was measured in a pre-/post-test design with the Intercultural Development Inventory (IDI). As a group, participants in the study slightly increased their scores on the IDI, with forward-stage movement and Perceived-Developmental Orientation gap decreases evident in roughly half of students. Implications of the findings, including the fit of the IDI for this context and limitations of the study design, are discussed.